Prognostic factors in endometrial cancer - Bajracharya , S R; Juan , F Y (Journal of Institute of Medicine Nepal, 2013)
Introduction: Endometrial cancer (EC) is the most common malignancy of the female genital tract. It is now the fourth most common gynecological cancer among women and the sixth worldwide cancer in Western countries. It is the most curable of the 10 most common cancers in women and the most frequent and curable of the gynecologic cancers. The incidence is increasing when life expectancy rise. This study was carried out to evaluate the prognostic factors of Endometrial Cancer. Methods: Clinico-pathological characteristics and follow-up cases of endometrial cancer were analysed retrospectively between January 2000 to December 2007 with its prognostic factors influence were statistically analysed. Results: During the study period total 180 patients were taken. Univariate model revealed that the menopausal status, the FIGO stage, grade, histological type, myometrial invasion, ER, PR, peritoneal cytology, lymph node metastases, adjuvant therapy, and the method of operation were related with the prognosis significantly. The multivariate analysis Cox proportion hazards regression model showed that the ER (P=0.004), PR (P=0.000), myometrial invasion (P=0.006) and lymph node metastases (P=0.049) were related with the prognosis significantly. Conclusion: The clinico- pathological character of endometrial cancer is responsible for patient’s better survival. If the patients had early detection and treated in proper modalities, this might improve the good prognosis.